Recharging China in War and Revolution, 1882-1955 - Tan, Ying Jia (Cornell University Press, 2021)
"In Recharging China in War and Revolution, 1882-1955, Ying Jia Tan explores the fascinating politics of Chinese power consumption as electrical industries developed during seven decades of revolution and warfare. Tan traces this history from the textile-factory power shortages of the late Qing, through the struggle over China's electrical industries during its civil war, to the 1937 Japanese invasion that robbed China of 97 percent of its generative capacity. Along the way, he demonstrates that power industries became an integral part of the nation's military-industrial complex, showing how competing regimes asserted economic sovereignty through the nationalization of electricity. Based on a wide range of published records, engineering reports, and archival collections in China, Taiwan, Japan, and the United States, Recharging China in War and Revolution, 1882-1955 argues that, even in times of peace, the Chinese economy operated as though still at war, constructing power systems that met immediate demands but sacrificed efficiency and longevity. Thanks to generous funding from the Andrew W. Mellon Foundation, through The Sustainable History Monograph Pilot, the ebook editions of this book are available as Open Access volumes from Cornell Open (cornellopen.org) and other repositories."